Pembuatan Bibliografi Beranotasi Koleksi Fiksi di Perpustakaan Dinas Kearsipan dan Perpustakaan Kabupaten Pesisir Selatan Berbasis Microsoft Access - Natin, Zelvi Yanatan; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper aims to describe the making of annotated bibliography of fiction collection in the Library of the Department of Archives and Library of the Pesisir Selatan District Based Microsoft access .The method used is descriptive method with techniques of data collectionÂ through observation and interviews. The observations were conducted directly to investigate the fiction collections in the Library of Archives and Library of the Pesisir Selatan District. The results obtained in direct observation, the number of fiction collections in the form of a novel in the Library of Archives and Library Department of Pesisir Selatan District were 101 titles of books with its copies of 134 pieces. Based on the discussion, it concluded that the compilation of fiction collection annotated bibliography in the Library of Archives and Library Department of Pesisir Selatan District were done through several stages as follows: the stages of making annotated bibliography as follows: 1) title determination; 2) collection of library materials or information investigation; 3) collection of library materials; 4) classification or classification; 5) keyword creation; 6) index preparation; 7) typing bibliographic texts; and 8) checking the final manuscrips, and procedures for annotated bibliography based on Microsoft Access as follows: (1) create a database file; (2) create tables and input data; (3) design forms; (4) create and add event procedure; (5) create and design a query; (6) make a report; (7) create and design the menu view. Keyword: bibliography, fiction, microsoft access.